The Concept, Essence, and Significance of Criminal Procedural Form - Polianskyi, Anton; Baulin, Oleg; Lushchyk, Ihor (Problems of legality, 2026)
The relevance of the research topic is determined by the need for scientific research aimed at solving the problem of criminal procedural form, which cannot be solved without clarifying its content. The purpose of the article is to define the concept, essence, and significance of criminal procedural form on the basis of existing developments in legal science on the issue of criminal procedural form and analysis of the current state of regulatory and legal regulation of criminal procedural activity in Ukraine. Using a combination of general scientific and special legal research methods, as well as systemic and structural-functional approaches to defining the interaction of individual elements of the criminal justice system, the article analyzes the current legislation of Ukraine, the state of investigative and judicial activities, linguistic interpretation, and philosophical approaches to the perception and legal content of criminal procedural form. It is emphasized that the successful adaptation of individual provisions of Ukraine’s criminal procedural legislation to the requirements of modern international standards largely depends on resolving the problem of understanding criminal procedural form. It has been established that criminal procedure reflects the content of criminal proceedings as defined by the legislator with regard to the order of criminal proceedings, which determines the structure of the proceedings, their organization, the order of each stage of the process, and procedural acts. The definition of criminal procedural form as the order of criminal proceedings established by criminal procedural legislation in general, the order of proceedings at each stage, as well as the order (procedure) for performing and formalizing individual procedural actions, adopting, formalizing, and enforcing procedural decisions is justified. The results of the study emphasize that the uniqueness of criminal procedure as a legal category is linked to its conceptual significance for the theory of criminal procedure law and the practical activities of criminal justice authorities, as it is a fundamental procedural guarantee of fair criminal proceedings and a universal means for the orderly formation and optimization of the criminal procedure system. Problems related to the improvement of both procedural norms and certain stages (phases) of criminal proceedings require priority research.